(untitled) (Nordic Journal of African Studies, 2005)
This paper investigated the perception and interpretation of a sub-class of sentence intonation by some Nigerian users of English. In a test administered to one hundred and twenty third-year university students of English, they obtained 85.7% correct perception of changes in intonation but obtained only 25.7% correct interpretation of the meanings normally associated with the intonation contours on the ten sentences played back to them. It was concluded from the analysis that the concept of intonation was well known to the subjects, though the attempt to teach them English intonation through its structural analysis appeared not to have been very successful. The study recommends that emphasis should be placed on the teaching of the social meaning of English intonation to non-native learners instead of the analysis of its phonological structure.